Students’ perspective on teaching quality determinants: a comparative study between social science and pure science students in the northern region universities / Roshima Said…[et al.] - Said, Roshima; Awang, Norasmila; Wan Omar, Maznah; Haji Husin, Zaliha (Research Management Institude, 2003)
The present study seeks to determine the possible criteria that would affect the level of teaching quality among academicians of Institute of Higher Learning from the students' perspective. Three universities in the Northern region were selected in this study, which include Universiti Teknologi MARA (UiTM) Kedah, Perlis and Pulau Pinang Branch Campuses, Universiti Sains Malaysia (USM), and Universiti Utara Malaysia (UUM). A sample of 500 Social Science and Pure Science students from the three universities was selected for this study. The findings showed that the teaching quality determinants that are ranked as very important to both social science and pure science students are as follows; Clarity, Feedback, Syllabus, Creativity, Practicality, Exercises, Attention, Enthusiasm, Availability, Approachable, Communication And Language Use. Moreover, the social science students also perceived the other five determinants i.e Motivation, Extra Reading, Technology, Punctuality and Current Issue as very important, while the pure science students perceived them as important except for current issue, which is perceived as not important.